2020
DOI: 10.1136/bmjopen-2019-032487
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and current practices of pregnant women towards group B streptococcus screening: cross-sectional study, Al-Madinah, Saudi Arabia

Abstract: AimsGroup B streptococcus (GBS) is one of the most frequent bacterial pathogens causing invasive infections in neonates. It can be transmitted from colonised mother to neonates around delivery. Screening strategies for GBS during pregnancy include either universal culture-based or risk-based screening. The present study aimed to assess the knowledge, attitude and current practices of pregnant women towards GBS screening in Al-Madinah City, Saudi Arabia.MethodsA hospital-based cross-sectional study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 15 publications
0
17
1
Order By: Relevance
“…The women's mean knowledge score was 50.7%, which was lower than that of the study conducted in Al Madinah (58.8%) [7]. The lower score might be because 86.6% of them had never been informed of GBS risks during pregnancy.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…The women's mean knowledge score was 50.7%, which was lower than that of the study conducted in Al Madinah (58.8%) [7]. The lower score might be because 86.6% of them had never been informed of GBS risks during pregnancy.…”
Section: Discussioncontrasting
confidence: 68%
“…Another possible explanation for this lack of awareness is the large number of participants who had never had this infection (97.3%), which is a large number given the reported rate of GBS colonization (9.2%-27.6%) during the third trimester among pregnant women [15]. A comparison of the findings with those reported in studies conducted by Alshengeti et al and Youden et al confirmed a low level of GBS awareness among women [7,16]. In addition, only 7% of women have been requested to undergo GBS testing by their gynecologists, whereas 81.7% of pregnant women in Poland have been tested [17].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Group B Streptococcus (GBS) is an important cause of infection in maternal and neonatal in many countries in the world (15,16). The most important risk factor of the infectious disease in the neonatal in developing countries was maternal GBS colonization (17).…”
Section: Discussionmentioning
confidence: 99%